2005
DOI: 10.1038/sj.bjc.6602509
|View full text |Cite
|
Sign up to set email alerts
|

Gastrin stabilises β-catenin protein in mouse colorectal cancer cells

Abstract: As gastrin may play a role in the pathophysiology of gastrointestinal (GI) malignancies, the elucidation of the mechanisms governing gastrin-induced proliferation has recently gained considerable interest. Several studies have reported that a large percentage of colorectal tumours overexpress or stabilise the b-catenin oncoprotein. We thus sought to determine whether gastrin might regulate b-catenin expression in colorectal tumour cells. Amidated gastrin-17 (G-17), one of the major circulating forms of gastrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…2A). p␤-Cat 33,37,41 , on the other hand, increased significantly after NEMO treatment, suggesting that NEMO may be facilitating activation of kinases such as GSK-3␤, thereby promoting phosphorylation of ␤-catenin at serine 33 and 37 residues in P colonic crypts. Bar graphs in Fig.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…2A). p␤-Cat 33,37,41 , on the other hand, increased significantly after NEMO treatment, suggesting that NEMO may be facilitating activation of kinases such as GSK-3␤, thereby promoting phosphorylation of ␤-catenin at serine 33 and 37 residues in P colonic crypts. Bar graphs in Fig.…”
Section: Resultsmentioning
confidence: 98%
“…As a continuation of the studies, the possible contribution of the Wnt/␤-catenin pathway was examined in the observed biological effects of progastrin. Casein kinase I⑀ (CKI⑀) and GSK-3␤ phosphorylate ␤-catenin at Ser 45 (p␤-cat 45 ) and Thr 41 /Ser 37,33 (p␤-cat 33,37,41 ) residues, thereby facilitating its ubiquitination and proteasomal degradation (20). Total crypt extracts, probed by Western blotting, demonstrated significant increases in levels of p␤-cat 45 in proximal colons of Fabp-PG (Tg) versus WT mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several Wnt target genes (Gastrin, FGF, c-Met, Tiam1, and Pygopus) are known to activate the Wnt/b-catenin signaling pathway (25)(26)(27)(28)(29). Gastrin, which plays a central role in the pathophysiology of gastrointestinal malignancies, enhances Figure 1.…”
Section: Phospholipase D Activates Wnt/b-catenin Signaling Via a Posimentioning
confidence: 99%
“…b-catenin/TCF-dependent transcription activity through stabilization of b-catenin in colorectal cancer cells (25). FGF stabilizes b-catenin by downregulating GSK3b activity (26).…”
Section: Phospholipase D Activates Wnt/b-catenin Signaling Via a Posimentioning
confidence: 99%